2021
DOI: 10.1093/g3journal/jkab221
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transmission and recombination of Wolbachia in the butterfly tribe Aeromachini Tutt, 1906 (Lepidoptera: Hesperiidae)

Abstract: Wolbachia is arguably one of the most ubiquitous heritable symbionts among insects and understanding its transmission dynamics is crucial for understanding why it is so common. While previous research has studied the transmission pathways of Wolbachia in several insect lineages including Lepidoptera, this study takes advantage of data collected from the lepidopteran tribe Aeromachini in an effort to assess patterns of transmission. Twenty-one of the 46 species of Aeromachini species were infected with Wolbachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Wolbachia -positive individuals were previously identified in Wisconsin populations of A. idalia ( Hamm et al 2014 ), although the specific strain type was not determined. The high prevalence of strain type 41 infection in both A. aphrodite (100% of tested individuals) and A. cybele (~40% of tested individuals) at FIG-NGTC is concerning, however, given research suggesting horizontal transfer of Wolbachia endosymbionts is more successful among closely related hosts ( Russell et al 2009 , Zhao et al 2021 ), especially those that share food sources ( Ahmed et al 2016 ), as is commonly observed at FIG-NGTC (data not shown). Monitoring for Wolbachia infection status in the FIG-NGTC eastern regal fritillary population will therefore play a crucial role in on-going conservation strategies, including captive rearing and reintroduction efforts, as shown in similar studies ( Nice et al 2009 , Fenner et al 2017 , Daniels et al 2018 , Dincă et al 2018 ).…”
Section: Discussionmentioning
confidence: 86%
“…Wolbachia -positive individuals were previously identified in Wisconsin populations of A. idalia ( Hamm et al 2014 ), although the specific strain type was not determined. The high prevalence of strain type 41 infection in both A. aphrodite (100% of tested individuals) and A. cybele (~40% of tested individuals) at FIG-NGTC is concerning, however, given research suggesting horizontal transfer of Wolbachia endosymbionts is more successful among closely related hosts ( Russell et al 2009 , Zhao et al 2021 ), especially those that share food sources ( Ahmed et al 2016 ), as is commonly observed at FIG-NGTC (data not shown). Monitoring for Wolbachia infection status in the FIG-NGTC eastern regal fritillary population will therefore play a crucial role in on-going conservation strategies, including captive rearing and reintroduction efforts, as shown in similar studies ( Nice et al 2009 , Fenner et al 2017 , Daniels et al 2018 , Dincă et al 2018 ).…”
Section: Discussionmentioning
confidence: 86%
“…In addition to the germ-line cells, it is known that a range of other somatic tissues can also be infected [77]. Moreover, horizontal transmission of Wolbachia between phylogenetically close and distant hosts, or directly from the environment, has been detected in many cases [78]. Thus, Wolbachia was considered to occur in non-arthropod hosts.…”
Section: Future Research Prospects: Losing or Winning With The Master...mentioning
confidence: 99%
“…Wolbachia strains are subdivided into 17 supergroups from A to R, except for supergroup G, which is controversial ( Baldo et al, 2006 ; Baldo and Werren, 2007 ; Wang et al, 2016 ; Zhao et al, 2021 ). The majority of Wolbachia strains found in insects belong to supergroups A and B.…”
Section: Wolbachia Phenotypesmentioning
confidence: 99%